Humble Chief Executive Officers’ Connections to Top Management Team Integration and Middle Managers’ Responses - Ou, Amy Y.; Tsui, Anne S.; Kinicki, Angelo J.; Waldman, David A.; Xiao, Zhixing; Song, Lynda Jiwen (Administrative Science Quarterly, 2014)
In this article, we examine the concept of humility among chief executive officers (CEOs) and the process through which it is connected to integration in the top management team (TMT) and middle managers’ responses. We develop and validate a comprehensive measure of humility using multiple samples and then test a multilevel model of how CEOs’ humility links to the processes of top and middle managers. Our methodology involves survey data gathered twice from 328 TMT members and 645 middle managers in 63 private companies in China. We find CEO humility to be positively associated with empowering leadership behaviors, which in turn correlates with TMT integration. TMT integration then positively relates to middle managers’ perception of having an empowering organizational climate, which is then associated with their work engagement, affective commitment, and job performance. Findings confirm our hypotheses based on social information processing theory: humble CEOs connect to top and middle managers through collective perceptions of empowerment at both levels. Qualitative data from interviews with 51 CEOs provide additional insight into the meaning of humility among CEOs and differences between those with high and low humility.